The effect of vitamin D deficiency on the RANKL/OPG ratio in rats - Rawan M. Khalaf; Abdullazez A. Almudhi (Elsevier, 2022)
The aim of this study was to determine the effect of vitamin D deficiency on the RANKL/OPG ((Receptor Activator of Nuclear Factor Kappa B Ligand/Osteoprotegerin) ratio in the serum blood levels. Sixteen Wistar rats were divided into 2 groups: a control group (C) and an experimental group (E). The group C comprised of rats with average vitamin D levels, while vitamin D deficiency was induced in those of group E. A test period of 21 days was employed wherein two serum blood samples were obtained, at the baseline (day 0) and at day 21. Changes in RANKL andOPG levels were measured using Enzyme-linked immunosorbent assay (ELISA) kits. A statistically significant decrease of serum RANKL concentration and RANKL/OPG ratio on day 21 was seen in the experimental group compared to the control group. The serum RANKL levels and RANKL/OPG ratio in rats, were negatively affected by the deficiency of vitamin D.